Ecology and behaviour of long-tailed macaques (Macaca fascicularis Raffles) at Kuala Selangor Nature Park, Malaysia - Kambali, Kamarul Ariffin (2016)
An ecological and behavioural study was carried out on long-tailed macaques (Macaca fascicularis) at Kuala Selangor Nature Park (KSNP), Selangor. This study was conducted to obtain a better understanding about social organization, ranging behaviour, food selection, activity budget, pest behaviour and also human-macaque conflict. Nowadays, economic growth and a rapid increase in human population have resulted in a widespread violation on forest habitat, resulting in the burgeoning of human-nonhuman primate conflict due to the crop raiding activity by the macaques and more recently, pest behaviour in urban environments as they exploit garbage and other human food sources. Fieldwork has focused on the activity of following the study groups, which was selected at the preliminary observation, and observing their behaviour using instantaneous scan sampling method. This study was conducted over 11 months from February 2011 to December 2011 for the outside group while for the inside group, it also involved 11 months of timeline from January 2014 to November 2014. At the study area, M. fascicularis has indicated significant difference in the size of the group whereby the outside group of KSNP have larger group size (40±0.9 individuals) in comparison with the inside group size of (30±0.9 individuals). Both study groups limit their movements in the core area of their home range and occupy the area repeatedly, which has shown a strong preference for the area and a very familiar path. The factors that can influence the movement patterns of both study groups were the distribution of food and also sleeping sites preference. For the sleeping sites preference, M. fascicularis used the limited sleeping sites and tend to sleep at their favourite sleeping sites repetitively. While the use of canopy strata, M. fascicularis were mostly found to choose ground level and also lower canopy compared to other levels of trees canopy. The outside group in the study area had a strong priority in choosing other food (anthropogenic food) (27.79%), followed by fruits (22.85%), mature leafs (18.95%), flowers (12.44%), young leafs (11.41%), seeds (4.18%), shoots (1.57%), insects (0.73%) and animals (0.09%) as their food. In contrast, the inside group has more preference in choosing fruits (37.91%), followed by insects (34.42%), mature leafs (8.34%), young leafs (8.26%), seeds (5.61%), shoots (2.96%), flowers (2.5%) and no consumption of animals and others food. The outside group spent a lot of their time to perform moving activities (21.89%) followed by feeding (19.16%), inactive (15.82%), grooming (10.74%), playing (10.67%), vocal interaction (9.81%), mating (6.54%) and the lowest activity was fighting (4.84%). For the inside group, they spent most of their time in moving (21.66%) followed by feeding (19.65%), vocal interaction (14.12%), grooming (11.97%), mating (11.79%), inactive (9.45%), playing (7.24%) and the lowest was fighting (4.11%). For pest behaviour, it was only recorded to be performed by the outside group. From the observations that have been carried out, the outside group spent a lot of their time to perform littering (27%), followed by damaging facilities (24%), breaking into human areas (18%), messing up garbage cans (18%), disturbing people (11%) and finally stealing (3%). Respondents from residential areas have more experience related to M. fascicularis disturbances compared with visitors. Overall, the study of the ecology and behaviour of M. fascicularis has run smoothly and has met the required answers according to the desired objectives. This study emphasizes on the ecological and behavioural strategies adopted by M. fascicularis to enable them to become the most successful animals as well as in creating conflict with people. Among the ecological and behavioural strategies that have been identified in this study are social organization, ranging behaviour, food selection, activity budget and also pest behaviour. All ecological parameters are the core of behaviour-ecological aspects that is influenced by the habitat that they lived in terms of food diversity, abundance, seasonal variation in productivity and other animal communities that lived in the area. As for the population status, the outside group would cause more problems to visitors and residents compared to the inside group. This is because they are more aggressive and involve in pest behaviour. Increased in human activity such as feeding the macaque, high amount of leftovers that are disposed into dustbins provided outside KSNP leads to more available food for the group. Some of the strategies that can be adopted for management purpose are inventing monkey-proof dustbin and maintaining certain numbers of macaque individuals at around 30 individuals at a time. This can be done through translocation process after understanding the social organization of the groups. Others strategies are also highlighted in the recommendations part. It is hoped that all of the information obtained from this study can be considered in the process of management and conservational effort of this species in the future.